2007
DOI: 10.1097/01.pec.0000280513.98289.e8
|View full text |Cite
|
Sign up to set email alerts
|

Lichen Sclerosus in the Differential Diagnosis of Suspected Child Abuse Cases

Abstract: Lichen sclerosus in young females can present as traumatic injuries on the vulva which can mimic sexual abuse. The case of an unconscious 6-year-old girl presenting in a reported inflicted drug overdose and with a clinical picture of ecchymosis and abrasions of the anogenital area is presented and discussed. The following case underscores the need for clinicians evaluating children for suspected abuse, to consider alternate conditions and causes that may not be related to sexual abuse.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 7 publications
(10 reference statements)
0
5
0
Order By: Relevance
“…Trauma, injury, and sexual abuse have been suggested as possible triggers of VLS in genetically predisposed people through the Köebner phenomenon mechanism. 31 An alarming but interesting study was performed by Warrington et al 19 on 42 girls affected by VLS. Among them, sexual abuse was confirmed in 12/42 cases (28.6%), suggesting that the diagnosis of VLS does not exclude coexistent sexual abuse.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Trauma, injury, and sexual abuse have been suggested as possible triggers of VLS in genetically predisposed people through the Köebner phenomenon mechanism. 31 An alarming but interesting study was performed by Warrington et al 19 on 42 girls affected by VLS. Among them, sexual abuse was confirmed in 12/42 cases (28.6%), suggesting that the diagnosis of VLS does not exclude coexistent sexual abuse.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the diagnosis offers many challenges to the clinician. Trauma, injury, and sexual abuse have been suggested as possible triggers of VLS in genetically predisposed people through the Köebner phenomenon mechanism 31 . An alarming but interesting study was performed by Warrington et al 19 on 42 girls affected by VLS.…”
Section: Discussionmentioning
confidence: 99%
“…Ecchymoses are almost pathognomonic of genital LS. In girls, these violaceous macules should not be misinterpreted as a result of sexual abuses [17].…”
Section: Signsmentioning
confidence: 99%
“…), infections or also sexual abuse are thought to increase the efflorescences. This socalled Koebner response appears to have a triggering function [5]. The diagnosis of LS therefore in no way rules out previous sexual abuse.…”
Section: Discussion ▼mentioning
confidence: 99%
“…In the literature available to us there are only isolated reports about difficult differentiations between LS and sexual abuse. For example, Isaac et al reported about a similar case in the USA with tragic consequences of the attempted further suicide of the child's mother [5]. In Saudi Arabia, Al-Khenaizan et al reported about a 3yearold girl with LS.…”
Section: Discussion ▼mentioning
confidence: 99%